Cross-Cultural Adaptation and Psychometric Validation of H-PEPSS in Indonesian Diploma-III Nursing Students - Linda, Silvana Evi; Lindayani, Linlin (The Indonesian Institute of Science and Technology Research, 2025)
In Indonesia, there is currently no standardized tool to evaluate patient safety competence among nursing students. This study aimed to culturally adapt and test the H-PEPSS for use with Indonesian nursing students. The participants were final-year diploma nursing students from Jakarta and West Java. The process included translation, expert validation, pilot testing, and cultural adaptation using cognitive interviews and student feedback. Items were developed through domain analysis and reviewed by experts to ensure relevance and clarity. The validity of the measurement model was examined using RMSEA, SRMR, and CFI indices, while internal consistency was tested to assess reliability. A total of 344 students from eight institutions in Jakarta and Bandung took part in the psychometric testing. The Content Validity Index (CVI) ranged from 0.73 to 1.00 across items. Pearson correlation coefficients varied by domain. The three-factor structure showed a good model fit, with standardized factor loadings above 0.4. All indicator variables exceeded the 0.30 significance threshold. The Indonesian version of H-PEPSS demonstrated a Cronbach’s alpha of 0.795, indicating acceptable reliability. The results suggest that H-PEPSS is a suitable instrument for assessing patient safety competencies among Indonesian nursing students and can be successfully adapted for use in different cultural settings.